Accumulation of a Last Deglacial Gravel Layer at Diexi, Eastern Tibetan Plateau and its Possible Seismic Significance - Zhang, Siqi; Jiang, Hanchao; Fan, Jiawei; Xu, Hongyan; Shi, Wei; Guo, Qiaoqiao; Wei, Xiaotong (Frontiers in Earth Science, 2021)
Tectonic and climatic process controlling gravel accumulation in tectonically active regions is the subject of active debate. In this study, the formation mechanism of a gravel layer in the Diexi lacustrine section, eastern Tibetan Plateau, was investigated using mutually validated dating methods and detailed analysis of sedimentary processes. Optically stimulated luminescence (OSL) and accelerator mass spectrometry (AMS) 14C dating show that the gravel layer in the Diexi section accumulated at approximately 16.79 ka BP. The sedimentary characteristics of the gravel layer and the contact between upper and lower strata indicate that the formation of the Diexi gravel layer was triggered by an earthquake rather than by a debris flow caused by torrential rain. And the result based on the intensity attenuation model are consistent with the characteristics of frequent large earthquakes in Diexi area. Detailed analysis of satellite images and sedimentary characteristics of the gravel layer provide evidence for an ancient landslide, which may be related to the gravel layer at Muer village (to the north of the Diexi section). Overall, this study reconstructs a gravel event at approximately 16.79 ka BP and has important theoretical and practical significance for understanding the formation mechanism of gravel deposits and analysing seismic events through gravel accumulation.